2022
DOI: 10.1186/s12951-022-01639-8
|View full text |Cite
|
Sign up to set email alerts
|

Platelet membrane-camouflaged nanoparticles carry microRNA inhibitor against myocardial ischaemia‒reperfusion injury

Abstract: The incidence of myocardial ischaemia‒reperfusion injury (MIRI) is increasing every year, and there is an urgent need to develop new therapeutic approaches. Nrf2 is thought to play a protective role during MIRI and it is regulated by microRNAs (miRNAs). This study focused on PLGA nanoparticles camouflaged by platelet membrane vesicles (PMVs) (i.e., PMVs@PLGA complexes) carrying microRNA inhibitors, which regulate Nrf2 and can play a therapeutic role in the MIRI process. In vitro and in vivo characterization sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…[100] Inspired by the cardioprotective ability of Nrf2 during MIRI, Wang et al identified miR-155-5p, a microRNA that effectively regulates Nrf2 and mediates MIRI, and formulated PNPs containing inhibitors of miR-155-5p for the treatment of MIRI. [101] The researchers encapsulated miR-155-5p inhibitors within PLGA NPs using a double emulsion technique known for its high transfection efficiency. Subsequently, the resulting PNPs were coated with PM using ultrasound.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…[100] Inspired by the cardioprotective ability of Nrf2 during MIRI, Wang et al identified miR-155-5p, a microRNA that effectively regulates Nrf2 and mediates MIRI, and formulated PNPs containing inhibitors of miR-155-5p for the treatment of MIRI. [101] The researchers encapsulated miR-155-5p inhibitors within PLGA NPs using a double emulsion technique known for its high transfection efficiency. Subsequently, the resulting PNPs were coated with PM using ultrasound.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…[ 14 ] Under physiological conditions, Nrf2 plays an important role in reducing oxidative stress, endoplasmic reticulum stress, and mitochondrial repair, reducing inflammation and autophagy, and protecting cardiomyocytes during MIRI. [ 15 ] Interestingly, two potential targets of Nrf2 inactivation that may cause ferroptosis, xCT and glutathione peroxidase 4 (GPX4), are well confirmed to be controlled by Nrf2. [ 16 ] The level of Nrf2 has been correlated with ferroptosis sensitivity because Nrf2‐downregulated cancer cells are susceptible to ferroptosis‐promoting drugs, and the occurrence and execution of ferroptosis could be prevented by overexpression of Nrf2.…”
Section: Introductionmentioning
confidence: 99%
“…19 These widespread applications are attributed to their outstanding properties such as prolonged circulation, immune evasion, and targeting capability. 20 Red blood cell membrane-coated nanoparticles (RBCNPs) were the first platform to be employed, 21 followed by platelets, 22 tumor cells, 23 and macrophages. 24 These bionic NPs retain the biological function of the source cells.…”
Section: Introductionmentioning
confidence: 99%